HUBUNGAN BEBAN KERJA PERAWAT DENGAN RESPONSE TIME PADA PENANGANAN PASIEN DI IGD (INSTALASI GAWAT DARURAT) RSU KABUPATEN TANGERANG TAHUN 2021 - Afifah, Risa; Wreksagung, Hyang; Sari, Rina Puspita (Nusantara Hasana Berdikari, 2022)
The nursing services provided by the emergency room are very complex, so there will be a risk of increasing the workload of nurses who are excessive. The workload affects the accuracy and speed of service. Therefore the standard response time 5 minutes is an indicator that determines the quality of each service. Research objective to find out whether there is a relationship between nurse workload and response time in patient care. Research Methods: This study uses quantitative methods and cross sectional research design. This study amounted to 44 respondents who were taken by total sampling. The analysis used in this study is univariate and bivariate analysis using the Chi Square (ê“Â²) test. Research Results: The results of the Chi-Square Test analysis that has been carried out, it is known that the significance value of value = 0.606 or = > 0.05, it can be concluded that there is no significant relationship between workload and nurse response time in the IGD RSU Tangerang Regency.